Development of problem-based learning worksheets on sequences and series to facilitate students' mathematical creative thinking skills - Permata, Ariya; Solfitri, Titi; Anggraini, Rini Dian (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The ability to think creatively in mathematics is a crucial aspect of learning, yet evidence shows that students' creative mathematical thinking skills, particularly in the topic of Sequences and Series, remain low. One solution to address this issue is through the use of Problem-Based Learning (PBL)-based Student Worksheets. This research aims to develop a valid and practical Student Worksheet. The study follows the 4D development model, consisting of the stages: define, design, develop, and disseminate. The instruments used for data collection were validation sheets and practicality questionnaires. Analysis of the validation sheet data showed that the Student Worksheet was categorized as highly valid, with an average percentage of 93.73%. Similarly, the practicality questionnaire analysis indicated that the Student Worksheet was rated as practical, with an average percentage of 83.77%. Therefore, the developed Student Worksheet meets the criteria of validity and practicality and can be used effectively in learning activities. The implication of this research is that it allows students to independently build knowledge in mathematics, facilitating their creative mathematical thinking skills.